Volcanic Setting of the 1.8-1.9 Ga. Eisenbrey Cu-Zn Deposit, Rusk County, Wisconsin - Hessburg, Jeffrey; Lodge, Robert W.D. (My University, 2019)
The objective of this research is to complete a petrographic and geochemical characterization of the least-altered volcanic rocks hosting the Eisenbrey Cu-Zn deposit in Rusk County, WI. This study builds on previous UWEC student research on the Eisenbrey deposit (Jackson et al, 2016). Major and trace element geochemical data was used to assess the magmatic characteristics of the volcanic system that formed the Eisenbrey ore body. In addition, the geochemical data will be used to characterize the stratigraphy and hydrothermal alteration hosting the Eisenbrey ore body and will ultimately allow for the reconstruction of the physical volcanology and tectonic se􀆫ng that created this deposit. Reconstructing the Eisenbrey volcanic system will lead to a better understanding of the tectonic history of the 1.8-1.9 Ga Penokean orogen in northern Wisconsin. The analyses will also aid to give a better understanding on the petrogenesis and metallogeny of the volcanogenic massive sulfide deposits in the region.
Color poster with text, images, charts, photographs, and graphs.
Keywords: Subsurface geology; Rusk County (Wis.); Posters